Logic, Language, Information, and Computation: 27th International Workshop, WoLLIC 2021, Virtual Event, October 5-8, 2021, Proceedings - Workshop on Logic, Language, Information and Computation; Silvia, Alexandra; Wassermann, Renata; Queiroz, Ruy de (Lecture Notes in Computer Science, 2021)
Edited in collaboration with FoLLI, the Association of Logic, Language and Information this book constitutes the refereed proceedings of the 27th Workshop on Logic, Language, Information and Communication, WoLLIC 2021, Virtual Event, in October 2021. The 25 full papers presented included 6 invited lectures were fully reviewed and selected from 50 submissions.The idea is to have a forum which is large enough in the number of possible interactions between logic and the sciences related to information and computation.